The influence of light on Interleukin-10: A preliminary study - Mekschrat, Liza; Göring, Michael; Schmalbach, Bjarne; Rohleder, Nicolas; Petrowski, Katja (Brain, Behavior, & Immunity-Health, 2024)
Light influences circadian rhythms, including that of the stress hormone cortisol. Cortisol, in turn, has been observed to promote expression of the anti-inflammatory cytokine IL-10. It is thus of interest whether the cytokine IL-10 is also influenced by light, perhaps in accord with the diurnal variations in cortisol. Hence, this highly standardized preliminary sleep laboratory study in healthy adult men investigated a potential influence of different light exposure on IL-10 and cortisol concentrations in blood. In a between-subject design, N = 42 participants were exposed to either bright, dim, blue or red light after wake-up. Two mixed-model analyses with the factors of light condition and time (across eight IL-10 and cortisol sampling points) were conducted. Additionally, area under the curve measurements (AUCg and AUCi) were calculated for both cortisol and IL-10. Across all conditions, IL-10 and cortisol concentrations significantly changed over time. However, none of the light conditions exerted a greater influence on IL-10 or cortisol levels than others. For cortisol, there was greater total output (AUCg) in the blue-light condition in particular. Further research is needed to gain insight into whether or not types of light or cortisol levels have a hand in influencing natural IL-10 concentrations.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Circadian rhythms; Cortisol awakening response; IL-10; Light irradiation